Inculcating a Corporate Revolution in the New Millennium - Garg, Naveen Kumar; Garg, Aditi (Journal of Commerce and Trade, 2008)
The corporate atmosphere is focused on the upbringing of a revolution in their work culture, performance and operating results in the long term. Business and corporate houses of India actively participate in canvassing the picture of new India in the new millennium. The basic idea is to draw attention towards the changes required in adoption of mission, objectivity, strategy and ethics by the businesses and how to grab the opportunities lying in the international markets. A guiding hand is mandatory in these conditions to handle the crisis of values in managing funds, stocks, and human resources at work.